2005
DOI: 10.1188/05.onf.1151-1163
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms for Chemotherapy-Induced Impairments in Cognitive Function

Abstract: The ability to identify high-risk patients has important implications for practice in regard to informed consent, patient education about the effects of treatment, and preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 85 publications
2
68
0
3
Order By: Relevance
“…This suggests that chemotherapy drugs have mechanisms that harm cognitive function. The evidence cognitive dysfunction by chemotherapy drugs are shown in a study that reported that the mechanisms causing such harms are leukoencephalopathy and the inflammatory response in the brain, both induced by the responses of cytokines, anemia, and early menopause (13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that chemotherapy drugs have mechanisms that harm cognitive function. The evidence cognitive dysfunction by chemotherapy drugs are shown in a study that reported that the mechanisms causing such harms are leukoencephalopathy and the inflammatory response in the brain, both induced by the responses of cytokines, anemia, and early menopause (13) .…”
Section: Discussionmentioning
confidence: 99%
“…The protocols involved in this study are described as triggers of leukoencephalopathy (5-FU, Methotrexate, Paclitaxel, and Cyclophosphamide) and inducers of the inflammatory process (Doxorubicin) that harm the cognitive function, causing, for instance, lack of concentration, reduced visual and spatial ability, and reduced memory (13) . The side effects also affected the CF, with the smallest means in patients with the strongest gastrointestinal, physical, and emotional symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these cytokines further compromise muscle endurance through their effect on lean tissue loss and anemia, and are also associated with decreased cognition and fatigue [14,15,32,37,42], two of the other core concepts in the EFF. C-reactive protein (CRP), an acute phase protein synthesized by the liver in response to cytokines released in the early phase of inflammation, is a well-established marker of systemic inflammation in advanced cancer [17,22].…”
Section: Muscle Mass Muscle Strength and Functionmentioning
confidence: 99%
“…Protective individual characteristics may include intelligence and educational levels. Factors that may increase risk include: concomitant effects of breast cancer and its treatment (e.g., medications, fatigue, depression, anxiety), indirect and direct effects of chemotherapy (e.g., chemotherapy-induced anemia or menopause), as well as individual patient characteristics (e.g., increasing age, menopausal status) [15].…”
Section: Introductionmentioning
confidence: 99%